2010
DOI: 10.1093/carcin/bgq128
|View full text |Cite
|
Sign up to set email alerts
|

FGFR2 and other loci identified in genome-wide association studies are associated with breast cancer in African-American and younger women

Abstract: Twenty-nine single-nucleotide polymorphisms (SNPs) from previously published genome-wide association studies (GWAS) and multiple ancestry informative markers were genotyped in the Carolina Breast Cancer Study (CBCS) (742 African-American (AA) cases, 1230 White cases; 658 AA controls, 1118 White controls). In the entire study population, 9/10 SNPs in fibroblast growth factor receptor 2 (FGFR2) were significantly associated with breast cancer after adjusting for age, race and European ancestry [odds ratios (OR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
114
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 24 publications
12
114
2
Order By: Relevance
“…H19 is transcribed in an untranslated RNA molecule that lacks conserved open reading frames but does have a conserved secondary RNA structure which accumulates in the human placenta and several fetal tissues, and probably plays a pivotal role in embryogenesis and fetal growth and tumor development [21]. Emerging evidences have shown that H19 was overexpressed in many types of cancer including hepatocellular [22], bladder [23], colon [24], and breast cancer [25]; however, the underlying role and mechanism of H19 involved in GC remains unclear. Recently, H19 was reported to act as a sponge to antagonize miRNAs, for example, let-7.…”
Section: Discussionmentioning
confidence: 99%
“…H19 is transcribed in an untranslated RNA molecule that lacks conserved open reading frames but does have a conserved secondary RNA structure which accumulates in the human placenta and several fetal tissues, and probably plays a pivotal role in embryogenesis and fetal growth and tumor development [21]. Emerging evidences have shown that H19 was overexpressed in many types of cancer including hepatocellular [22], bladder [23], colon [24], and breast cancer [25]; however, the underlying role and mechanism of H19 involved in GC remains unclear. Recently, H19 was reported to act as a sponge to antagonize miRNAs, for example, let-7.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should include patients from other areas in China and with a much larger sample size. a significant association has been demonstrated between the presence of the FGFR2 rs11200014 SNP and the incidence of breast cancer in European Caucasians (Hunter et al 2007), Ashkenazi and Sephardi Jews (Raskin et al 2008), and african-americans (Barnholtz-Sloan et al 2010). However, there appears to be no statistical correlation between this SNP and breast cancer risk in the Japanese, neither in premenopausal nor in postmenopausal women (Kawase et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that rs1219648A/G, rs2420946C/T, and rs2981582C/T in the second intron of FGFR2 were significantly associated with increased breast cancer risk in Chinese women, and the associations appeared to be stronger in premenopausal women (Liang et al 2008). Barnholtz-Sloan et al (2010) reported that among africanAmerican women, 4 SNPs (rs11200014, rs2981579, rs1219648, and rs2420946) in the second intron of FGFR2 were highly associated with increased breast cancer risk. Our current data revealed that the 4 SNPs rs11200014, rs1219648, rs2420946, and rs2981582, but not rs2981579, in the second intron of FGFR2, and the haplotype aGTT in these SNPs, were associated with an earlier age of onset (≤ 35 years) of sporadic breast cancers in Chinese women.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found 32 additional risk loci shared between early-and late-onset BC 123 . The second GWAS, which included Caucasian and African-American women with BC, detected a significant association between the GTGT haplotype (rs11200014, rs2981579, rs1219648 and rs2420946) in fibroblast growth factor receptor 2 and the risk of early onset BC 124 .…”
Section: Gwasmentioning
confidence: 99%